Marginal Railway Infrastructure Costs in a Dynamic Context - Andersson, Mats (European Journal of Transport and Infrastructure Research, 2008)
In this paper, dynamic aspects of railway infrastructure operation and maintenance costs in Sweden are explored. Econometric cost functions are estimated to check the robustness of previous marginal cost estimates by introducing lags and leads of both dependent and independent variables. We find support for a forward-looking behaviour within the Swedish National Rail Administration (Banverket) as both infrastructure operation and maintenance costs are reduced prior to a major renewal. There are also indications of both lagged traffic and costs affecting the cost structure.